Children and Terrorism : Human Rights for Indonesian Cubs of Caliphate - Gitaningrum, Indah (JURNAL PENELITIAN, 2021)
This study examines the complex relationship between children’s involvement in terrorist activities and the violation of their fundamental human rights, with particular focus on their freedom of religion or belief. The phenomenon of child involvement in terrorism in Indonesia has developed into a disturbing trend, with families directly participating in terrorist attacks, as exemplified by the 2018 Surabaya bombings. Indonesia, home of the world’s largest Muslim population, continues to confront the issue of radicalization. However, the increasing participation of children in terrorism calls for urgent attention to human rights concerns. This research employs a qualitative methodology, combining a literature review and interviews with officers at BRSAMPK Handayani Jakarta, to investigate the extent of children’s victimization in the context of terrorism. The findings reveal that children involved in terrorist activities should be viewed as victims rather than perpetrators, as their participation is driven by coercive ideological indoctrination which systematically violates their fundamental rights. The study emphasizes that such indoctrination deprives children of their autonomy, subjecting them to psychological manipulation and religious misinterpretation that strips them of their freedom of belief. Therefore, this paper recommends a strengthened policy framework to protect children from radicalization and ensure their rehabilitation through comprehensive deradicalization programs. The findings have significant implications for policymakers, human rights advocates, and scholars in counterterrorism and child protection.